Two modes of peer review among adult writers: which is better? - Yong, Mei Fung; Lee, Geok Imm (The English Teachers Association in Korea, 2008)
This article reports on the findings of a qualitative study which investigated Malaysian postgraduate writers’ perceptions of their experiences and reflections on peer review sessions. The participants were enrolled in a Technical and Professional Communication course at a public university in Malaysia. As part of the class assignment, the students were required to write a research grant proposal. These students carried out online and face-to-face reviews of their peer’s proposals before the final draft was submitted to the instructor. The reflections of their experiences on the peer review sessions were collected through journal entries and interviews. The data were then categorized into themes. The findings revealed that the students prefer face-to-face peer review. The reasons for their choice demonstrated a preference for a more immediate and direct feedback approach which the face-to-face review offers. The findings also showed that computer literacy, positive attitude, and familiarity with peers were important factors which contributed to the success of peer review.